Cost-effectiveness of serplulimab as first-line therapy for extensive-stage small cell lung cancer in China - Xiang, Guiyuan; Jiang, Tingting; Gan, Lanlan; Wu, Yuanlin; Zhang, Ni; Xing, Haiyan; Su, Hui; Li, Yanping; Peng, Dan; Ni, Rui; Liu, Yao (Frontiers in Immunology, 2023)
The ASTRUM-005 trial demonstrated that adding serplulimab to chemotherapy significantly prolonged the survival of patients with extensive-stage small cell lung cancer (SCLC), but also increased the risk of adverse events. Given the high cost of serplulimab compared to chemotherapy, this study aimed to evaluate the cost-effectiveness of serplulimab plus chemotherapy as a first-line treatment for extensive-stage SCLC from the perspective of China's healthcare system.Methods: A Markov model was developed to simulate the disease process of extensive-stage SCLC and estimate the health outcomes and direct medical costs of patients. Scenario analyses, univariate sensitivity analyses, and probabilistic sensitivity analyses were conducted to explore the impact of different parameters on model uncertainty. The primary model outcomes included costs, life-years (LYs), quality-adjusted life-years (QALYs), and the incremental cost-effectiveness ratio (ICER).Results: Compared to placebo plus chemotherapy, serplulimab plus chemotherapy resulted in an additional 0.25 life-years and 0.15 QALYs, but also increased costs by $26,402, resulting in an ICER of 179,161 USD/QALY. Sensitivity analysis showed that the ICER was most sensitive to the cost of serplulimab, and the probability that serplulimab was cost-effective when added to chemotherapy was only 0 at the willingness-to-pay threshold of 37,423 USD/QALY. Scenario analysis revealed that price discounts on serplulimab could increase its probability of being cost-effective.Serplulimab plus chemotherapy is not a cost-effective strategy for first-line treatment of extensive-stage SCLC in China. Price discounts on serplulimab can enhance its cost-effectiveness.